Pressure ulcers from prone positioning in COVID-19 patients: Developing clinical indicators in evidence-based practice: A retrospective study - Hassiel Aurelio Ramírez-Marín; Adrian Soto-Mota; Jorge Alanis-Mendizabal; Juan Manuel Escobar-Valderrama; Judith Guadalupe Domínguez-Cherit (Our Dermatology Online, 2022)
Background: A notable pandemic arisen during the COVID-19 pandemic has developed globally in intensive care units, with patients developing pressure ulcers (PUs) after being ventilated mechanically in the prone position. Objectives: The aim was to identify risk factors independently predictive of the development of PUs in adult patient populations treated with prone positioning and to evaluate a possible epidemiological association between the prevalence of PUs and specific clinical characteristics so as to develop clinical indicators for the prevention of PUs. Finally, the aim was to examine our study participants against the incidence of PUs with respect to the length of their stay. Methods: : This retrospective study enrolled patients hospitalized during the period of May 2020 through January 2021. Data was collected from 299 patients hospitalized and having required prone positioning ventilatory therapy in critical care areas (short-stay units, emergency units, and intensive care units), all of which had developed Pus of at least grade two according to the classification system proposed by the NPUAP/EPUAP. Results: : Patients who had developed PUs had a longer hospitalization stay overall and were more prone to die during hospitalization. Patients who developed Pus were more frequently males, with higher initial levels of CPK and ferritin. Conclusions: The study reveals valuable information on the most important risk factors in the development of PUs due to prone positioning. We have described how the total number of days of hospitalization is significantly related to the development of PUs. Even a PU is not a life-threatening lesion, the implementation of improved positioning protocols may enhance results in critical patient care. We believe that this is a current, globally underestimated problem as the incidence of COVID-19 patients requiring prone positioning-and, therefore, at risk for PUs-is increasing daily.